2011
DOI: 10.4304/tpls.1.11.1488-1496
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using Songs in YouTube to Improve Vocabulary Competence among Upper Secondary School Studies

Abstract: This study investigated whether learners exposed to songs using YouTube would experience a change in vocabulary competence compared to those exposed to the traditional teacher-fronted approach. To fulfil this purpose, 68 Form Four students were selected from a government-run secondary school located in Kedah, Malaysia. These participants were then divided into two equal groups of experimental and control. The study was carried out over a six-week course (12 sessions). A vocabulary test was administered as a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 2 publications
5
13
0
Order By: Relevance
“…Furthermore, Balcikanli (2011) reported that YouTube is an effective tool that facilitates students to retain the vocabulary that they learnt in the past without having to get bored. The results of such study confirmed the results of the study conducted by Abidin et al (2011) which reported that YouTube helps students to improve their vocabulary competence compared to a traditional method.…”
Section: Pre-test Versus Post-test Resultssupporting
confidence: 83%
“…Furthermore, Balcikanli (2011) reported that YouTube is an effective tool that facilitates students to retain the vocabulary that they learnt in the past without having to get bored. The results of such study confirmed the results of the study conducted by Abidin et al (2011) which reported that YouTube helps students to improve their vocabulary competence compared to a traditional method.…”
Section: Pre-test Versus Post-test Resultssupporting
confidence: 83%
“…Some videos on YouTube provide music and songs that enhance the vocabulary of the pupils. This has positive effects as said by Abidin Z et al (2011). This study also provides pupils with awareness of using YouTube videos in language learning.…”
Section: Research Question Twosupporting
confidence: 58%
“…Other studies related to the use of songs were also conducted (Albaladejo et al, 2018;Alisaari & Heikkola, 2017). A suggestion is also proposed to teach grammar (Roslim et al, 2011;Abdul Razak & Yunus, 2016;Akbary et al, 2016), vocabulary (Abidin et al, 2011), pronunciation (Villalobos Ulate, 2008) through songs. Most of the research has strongly recommended the use of songs to teach young learners.…”
Section: Introductionmentioning
confidence: 99%